The natural rate of interest in Brazil: state-space modelling approaches - Santos, Felipe Mecchi Garcia dos (2024)
This work focused on estimating the Natural Rate of Interest for Brazil, employing statespace modelling approaches with several combinations of input variables following three main references: the NRI estimation method proposed in Holston, Laubach and Williams (2023), the model proposed by Moreira and Portugal (2019), which estimates the NRI based on short and long interest rate maturities and the IS Curve proposed by Fonseca, Muinhos and Schulz (2022). Results obtained reiterate the downward trend frequently mentioned in the literature before the pandemic shock, after which the NRI started to rise once again: ranged from 1.6% to 4.5% in 2019 and between 3.6% and 5.75% in 2023. Estimating the NRI also allows to analyze the stance of monetary policy in Brazil, which can be summarized into five periods: (i) 2000-2006 predominantly contractionary – an adaptation period after the Plano Real; (ii) 1Q-2007 to 1Q-2014 a period with noticeably loose monetary policy; (iii) 2Q-2014 to 2Q-2019 a predominantly contractionary period even during a deep recession; (iv) 3Q-2019 to 2Q-2022 the stance went from neutral to expansionist, specially in the aftermath of the Covid-19 shock; (v) 3Q-2022 to 4Q-2023 a worldwide contractionary phase to cope with the high inflation that resulted from the unusually large stimuli employed after the pandemic shock.